ANXA5: related mechanisms of osteogenesis and additional biological functions - Jin, Ming; Zhang, Jingrun; Sun, Yimeng; Liu, Ge; Wei, Xiaowei (Frontiers in Cell and Developmental Biology, 2025)
Annexin A5 (ANXA5), also known as Annexin V, is a calcium-dependent phospholipid-binding protein and has a high affinity with phosphatidylserine (PS). This characteristic facilitates its involvement in a wide range of biological functions, including vesicle transport, the formation of mineral phases in the extracellular matrix, anticoagulation and antithrombotic, the inhibition of tumor growth, and apoptosis regulation. ANXA5 plays a role in anti-inflammatory and antithrombotic properties. It also has protective effects on the nervous system. ANXA5 has been reported to facilitate osteogenic differentiation and take part in chondrocyte apoptosis and mineralization. More and more attention is paid to the potential of ANXA5 for bone defect repair. Most current studies on ANXA5 mainly concentrate on immune disorders, pregnancy disorders and serve as a biomarker for various diseases as well as apoptosis detection. However, there is still a lack of systematic studies on ANXA5 involving multiple tissues, including bone, cartilage, vessels, and nerves in the process of bone regeneration. Our study aims to summarize the biological functions in bone tissue and the related signaling pathways of ANXA5. This work provides a theoretical foundation for applying ANXA5 in clinical orthopedics in the future.